2021
DOI: 10.1016/j.foodcont.2020.107595
|View full text |Cite
|
Sign up to set email alerts
|

Trace and rare earth elements determination in milk whey from the Veneto region, Italy

Abstract: , Y) in whey samples from cow and goat milk by inductively coupled plasma mass spectrometry and inductively coupled plasma-sector field mass spectrometry. A total of 261 milk whey samples were collected from four locations in the Veneto region of northeastern (NE) Italy. These samples contain a wide range concentration of 17 trace elements (0.06-1530 μg kg − 1) and 14 rare earth elements (0.16-28.2 ng kg − 1) in whey samples, but do not reach toxic concentrations. Elemental fingerprinting of trace and rare ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…From the results ( Table 3 ), it was found that the concentration of essential trace minerals in BCWP was in the order of sodium > calcium > magnesium > iron > selenium for trace elements. Furthermore, metals are non-biodegradable, which accumulate in the food chain through biotransformation ( Tedesco et al, 2021 ). Several authors ( Rahimi, 2013 , Temiz and Soylu, 2012 ) reported the occurrence of heavy elements (lead, mercury and cadmium) in whole milk or milk-based products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the results ( Table 3 ), it was found that the concentration of essential trace minerals in BCWP was in the order of sodium > calcium > magnesium > iron > selenium for trace elements. Furthermore, metals are non-biodegradable, which accumulate in the food chain through biotransformation ( Tedesco et al, 2021 ). Several authors ( Rahimi, 2013 , Temiz and Soylu, 2012 ) reported the occurrence of heavy elements (lead, mercury and cadmium) in whole milk or milk-based products.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, BCWP was analysed for heavy metals and the obtained results were tabulated in Table 3 . The level of heavy metals, Pb, As and Cd in milk-based whey of cows from the Veneto region, Italy was reported as 0.0002 ± 0.0001, 0.0013 ± 0.0005, 0.0062 ± 0.0010 mg kg −1 respectively ( Tedesco et al, 2021 ). The level of heavy metals (Mn, Cr, Ni, Cd, Pb, Hg, As) in sweet/acid concentrated whey was < 0.10 (ppm) ( Alsaed et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…), dietary habits and supplements. In similar studies, Tedesco et al (2021) [ 78 ], and Aceto et al (2017) [ 79 ] investigated the role of trace and rare earth elements in milk samples, throughout the production chain, from various regions of Italy. It was observed that the concentration of lanthanides remains nearly constant during the milk production and therefore were classified as suitable tracers.…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential implications to human health through excessive consumption of these products, it is important to develop sensitive and reliable analytical methods that can accurately identify and quantify element levels in protein powder products to ensure that they are safe for human consumption. Inductively coupled plasma-sector field mass spectrometry (ICP-SFMS) is a technique that offers the selectivity and sensitivity necessary to meet the analytical challenges of both simple and complex matrices [ 1 , 20 ], and it has been deployed successfully in recent years for the analysis of milk products [ 2 , 21 ]. Thus, the aim of this study is to develop a reliable ICP-SFMS method to assess the concentrations of essential/therapeutic elements in protein powder samples, as well as to investigate the possible potential risks to Irish consumers from exposure to these substances.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen below in Table 1 (adapted from Ring et al, 2016 [1]), the human body is comprised of these elements with many playing critical roles in metabolic processes, while others can cause negative side effects at certain concentrations. Balanced nutrition is therefore an essential aspect of maintaining health, as it allows our bodies to grow, repair and function and promotes overall health and wellbeing [2].…”
Section: Introduction Importance Of Elemental Monitoring and Regulation In Foodmentioning
confidence: 99%